Age‐related treatment patterns in sickle cell disease patients and the associated sickle cell complications and healthcare costs1. Issue 5 (17th January 2013) - Blinder, Morey A.; Vekeman, Francis; Sasane, Medha; Trahey, Alex; Paley, Carole; Duh, Mei Sheng
Abstract Background This study explored the blood transfusion patterns, SCD complications, utilization of iron chelation therapies (ICT), healthcare resource use, and costs in pediatric, transitioning (18 years old) and adult patients with SCD. Procedure Data from Florida (1998–2009), New Jersey (1996–2009), Missouri (1997–2010), Kansas (2001–2009), and Iowa (1998–2010) state Medicaid were used. Patients with ≥2 SCD diagnoses and ≥1 transfusion event were included. Rates of transfusion events, SCD complications, and proportion of eligible patients receiving ICT were calculated. ICT eligibility was defined as receiving ≥10 transfusions over lifetime. SCD complications included pain, pulmonary event, infection event, renal, cardiovascular, stroke, leg ulcers, and avascular necrosis. Regressions were used to assess risk factors for transfusion and identify the main drivers of costs. Results The sample included 3, 208 patients. The transfusion rate increased from 1‐year‐old to a peak at 16 years old, then dropped until age 26 and remained stable thereafter. In contrast the frequency of diagnoses for SCD complications increased markedly after age 16. Post‐transition patients (≥18 years old) were significantly associated with fewer transfusions (odds ratio: 0.80, P = 0.002). Among eligible patients for ICT, there was no statistically significant difference in total cost between the ICT and no ICT groups (adjusted cost difference, $136, P = 0.114). Conclusions Patients transitioning to adult care received less transfusions and hydroxyurea, less ICT when eligible for chelation therapy, had higher healthcare costs and suffered from more frequent SCD related complications than pediatric patients. These findings highlight the changes in treatment patterns corresponding to transition to adult care. Pediatr Blood Cancer 2013; 60: 828–835. © 2013 Wiley Periodicals, Inc.